Implementasi Pelayanan Administrasi Kependudukan Desa Kalimanah Wetan Purbalingga Berbasis Online - Ummu Radiyah; Dheska Ranita Setyowati; Anton anton (INFORMAL: Informatics Journal, 2019)
Implementation of Population Administration Services in the Village of Kalimanah Wetan Purbalingga is still done manually. In the processing of data population is still conventional with a data collection system that is now felt there are still many shortcomings that occur, because the existing system still uses sheets of paper so that it can cause existing data easily lost or damaged. The system development in the form of a web-based Population Service system in Kalimanah Wetan Village is a system that provides information on population data and web- based letter printing services, so as to help speed and quality in delivering information and simplify correspondence printing services to be more effective and efficient. In this system, the web can only be accessed by users, namely citizens and administrators. The method used in developing this system is SDLC (System Development Life Cycle) with the waterfall process model. In this study, besides describing the theoretical study that is used as the basis of the preparation, it will also be discussed regarding system design and the making of Population Services web. So that it is expected to be implemented in a product that will correct any shortcomings in the old system.